A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Membrane Damage Induced by Supercritical Carbon Dioxide in Rhodotorula mucilaginosa - Jun Li; Aiying Wang; Fengmei Zhu; Rui Xu; Xiao Song Hu (Indian Journal of Microbiology, 2013)

Genome-wide identification and transcription analysis of soybean carotenoid oxygenase genes during abiotic stress treatments - Rui-Kai Wang; Chun-E Wang; Yun-Yan Fei; Jun-Yi Gai; Tuan-Jie Zhao (Molecular Biology Reports, 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Effects of Ethephon on Key Enzymes of Sucrose Metabolism in Relation to Sucrose Accumulation in Sugarcane - Ai-Qin Wang; Wen-Jing Huang; Jun-Qi Niu; Ming Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Ion Beam Mutagenesis in Arthrobotrys oligospora Enhances Nematode-Trapping Ability - Jun Wang; Rui Wang; Xiaoye Yang (Current Microbiology, 2013)

Integrated application of 3D seismic and microseismic data in the development of tight gas reservoirs - Rui-Zhao Yang; Zheng-Guang Zhao; Wei-Jun Peng; Yu-Bo Gu; Zhan-Gang Wang; Xi-Qin Zhuang (Applied Geophysics, 2013)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Comparison of transcriptome under red and blue light culture of Saccharina japonica (Phaeophyceae) - Wen-Jun Wang; Fei-Jiu Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang (Planta, 2013)

Comparative study of the interactions between ovalbumin and three alkaloids by spectrofluorimetry - Rui-qiang Wang; Yu-jing Yin; Hua Li; Yi Wang; Juan-Juan Pu; Rui Wang; Huan-jing Dou; Chuan-jun Song; Rui-yong Wang (Molecular Biology Reports, 2013)

The effects of three years of fencing enclosure on soil seed banks and the relationship with above-ground vegetation of degraded alpine grasslands of the Tibetan plateau - Zhan-Huan Shang; Bin Deng; Lu-Ming Ding; Guo-Hua Ren; Guo-Sheng Xin; Zhi-Yun Liu; Yan-Long Wang; Rui-Jun Long (Plant and Soil, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Seed rain and its relationship with above-ground vegetation of degraded Kobresia meadows - Zhan-Huan Shang; Shi-Hai Yang; Jian-Jun Shi; Yan-Long Wang; Rui-Jun Long (Journal of Plant Research, 2013)